(untitled) (Research, Society and Development, 2021)
This dissertation aimed to understand how the process of building an innovative school space by its members has taken place. It established as a principle the perspective of the parents, mothers and educators involved in this path, who seeks the appreciation of the child and his issues in the construction process itself. In the theoretical basis, it sought the support of Walter Kohan, Walter Benjamin, Jorge Larrosa, Miguel Arroyo, Edgar Morin, Polianne Delmondez, José Pacheco, Regina Pedroza, Paula Sibilia and Lúcia Helena Pulino. The research, based on the qualitative methodology, with inspiration in cartography with observation procedures, semi-structured interviews and discussion with teachers, and field diary records. In the end, some factors were understood as possible contributions: the construction of the place as possibilities of understanding, problematizations and realization of a school space that considered the valuation of the child; the collective construction of a school; the role of fathers and mothers in contemporary society; and the challenge of becoming an educator, through reflection on what education can be: without answers or solutions to be applied, but with the formation of a community in constant reflection, showing itself as a unique and essential place of transformations.